2020
DOI: 10.1159/000506744
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Heart Disease: Prognostic Value of 5-Hydroxyindoleacetic Acid Levels and Impact on Survival: A Systematic Literature Review

Abstract: Background: Carcinoid heart disease (CHD) can develop in patients with carcinoid syndrome (CS), itself caused by overproduction of hormones and other products from some neuroendocrine tumours. The most common hormone is serotonin, detected as high 5-hydroxyindoleacetic acid (5-HIAA). This systematic literature review summarises current literature on the impact of CHD on survival, and the relationship between 5-HIAA levels and CHD development, progression, and mortality. Methods: MEDLINE, Embase, Cochrane datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
(178 reference statements)
3
20
0
Order By: Relevance
“…Previous studies have clearly demonstrated the role of serotonin using an assay of urinary 5‐HIAA in CaHD, 9 , 11 and in our study, we also found a significant increase of serotonin in patients presenting with CaHD. However, in a previous study, we reported that CaHD may progress in the first 3 years after the initial management of digestive endocrine tumor despite accurate therapeutic management.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have clearly demonstrated the role of serotonin using an assay of urinary 5‐HIAA in CaHD, 9 , 11 and in our study, we also found a significant increase of serotonin in patients presenting with CaHD. However, in a previous study, we reported that CaHD may progress in the first 3 years after the initial management of digestive endocrine tumor despite accurate therapeutic management.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have reported that the development of CaHD was related to an increased level of serotonin, previous use of chemotherapy, and the presence of a patent foramen ovale (PFO). 9 , 10 , 11 However, it is difficult to define an optimal follow‐up for patients initially free from cardiac involvement. The aim of this study was to assess the prevalence and the progression of CaHD nowadays by annual echocardiographic follow‐up.…”
mentioning
confidence: 99%
“…More pronounced valvular dysfunction may lead to increased right ventricular strain and eventual right-sided heart failure. CHD is associated with diminished survival [ 20 ], with a recent study demonstrating an approximately two-year reduction in median survival when compared to patients characterized by CS only [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This reuptake deficit could also explain the increased serotonin catabolism evidenced by the increase in urinary 5-HIAA in our work. This molecule is a product of the metabolism of serotonin whose stability in urines allows to have an appreciation of the level of activity of the serotonergic system as it is now clearly established in carcinoid heart disease [ 31 ]. We were able to show a link between the severity of the valve lesions, the platelet count and the urinary 5-HIAA thus showing the probable activation of the serotonergic system.…”
Section: Discussionmentioning
confidence: 99%